Odpowiedź :
Odpowiedź:
a) 1/3 x - 2 = x +2 /*3
x-6 = 3x +6
x - 3x = 6 + 6
-2x = 12 /:(-2)
x = -6
b)1 - 6/7x = 4/7 / * 7
7 - 6x = 4
-6x = -3 /:(-6)
x =1/2
c) 6( 1/4x -2) =18 /:6
1/4x - 2 = 3 / *4
x- 8 = 12
x = 20
d) x/6 - 1/6 = 1 / *6
x - 1 = 6
x = 7
e) -2 ( 2x -1) = x/3 / * 3
-6(2x -1) = x
-12x +6 = x
-13x = -6 / :(-13)
x = 6/13
f) 2/5 (3 - x) = -2 /: 2/5
3 - x = -2 : 2/5
-x = -8
x = 8
g) 3/4 (2-3x) = -6 /:3/4
2 - 3x = -6 : 3/4
-3x = -8 - 2
x = 10/3
h) 1/5 ( x - 3) = 9 - x /*5
x - 3 = 45 - 5x
x + 5x = 45 + 3
6x = 48
x = 8
i) (0,6 + x )/2 = x + 1 / * 2
0,6 + x = 2x + 2
x-2x = 2-0,6
- x = 1,4
x = - 1,4
Szczegółowe wyjaśnienie: